Gold, Uncertainty, Macroeconomy, Inflation Hedging and Safe Haven in Indonesia - Muhammad Edhie Purnawan; Inda Fresti Puspitasari (Economics Development Analysis Journal, 2021)
This study examines the impacts of monetary policy uncertainty and macroeconomic variables on gold price dynamics in Indonesia. Monthly time series data was used for the period of January 2009 till December 2018. Indonesia has the second place after Thailand as a country with the highest gold demand in Southeast Asia. but, there are less studies about role of gold as safe haven in Indonesia and this study is the first one that specifically included the uncertainty variable of US monetary policy in the model using ARDL-ECM approach. The ARDL-ECM approach is applied to find out are the gold price dynamics in Indonesia influenced by macroeconomic shocks or by the movements of gold price itself in the previous period. The empirical results of this study indicate that gold plays an important role as inflation hedging and safe haven in Indonesia. This study proved that in the short-term and long-term, gold price in the previous period, exchange rate, and IHSG have a negative and significant relationship on gold prices dynamics in Indonesia, while the London gold price and inflation have a positive and significant relationship on gold price movement in Indonesia. The high level of US monetary policy uncertainty and uncertainty in global economic conditions has led to an increase in gold prices in Indonesia.